Comparative analysis and gut bacterial community assemblages of grass carp and crucian carp in new lineages from the Dongting Lake area - Sheng Zou; Liang Gong; Tahir Ali Khan; Lifei Pan; Liang Yan; Dongjie Li; Lina Cao; Yanping Li; Xuezhi Ding; Ganfeng Yi; Yunjun Sun; Shengbiao Hu; et al. (MicrobiologyOpen, 2020)
Abstract Gut microbiota are known to play an important role in health and nutrition of the host and have been attracting an increasing attention. Farming of new lineages of grass carp and crucian carp has been developed rapidly as these species were found to outperform indigenous ones in terms of growth rate and susceptibility to diseases. Despite this rapid development, no studies have addressed the characteristics of their gut microbiota as a potential factor responsible for the improved characteristics. To reveal whether microbiomes of the new lineages are different from indigenous ones, and therefore could be responsible for improved growth features, intestinal microbiota from the new lineages were subjected to high‐throughput sequencing. While the phyla Firmicutes, Fusobacteria and Proteobacteria were representing the core bacterial communities that comprised more than 75% in all fish intestinal samples, significant differences were found in the microbial community composition of the new linages versus indigenous fish populations, suggesting the possibility that results in the advantages of enhanced disease resistance and rapid growth for the new fish lineages. Bacterial composition was similar between herbivorous and omnivorous fish. The relative abundance of Bacteroidetes and Actinobacteria was significantly higher in omnivores compared to that of herbivores, whereas Cetobacterium_sp. was abundant in herbivores. We also found that the gut microbiota of freshwater fish in the Dongting lake area was distinct from those of other areas. Network graphs showed the reduced overall connectivity of gut bacteria in indigenous fish, whereas the bacteria of the new fish lineage groups showed hubs with more node degree. A phylogenetic investigation of communities by reconstruction of unobserved states inferred function profile showed several metabolic processes were more active in the new lineages compared to indigenous fish. Our findings suggest that differences in gut bacterial community composition may be an important factor contributing to the rapid growth and high disease resistance of the new fish lineages.